Pemanfaatan Augmented Reality Dalam Memvisualisasikan Produk Perumahan Melalui Internet - Bonny A Suryawinata (Bina Nusantara University, 2010)
To attract house buyers, many ways is done by the developers to promote their products, such as by using multiple marketing medias namely television, radio, internet, newspapers or distribute flyers during the exhibition. It is not uncommon that the said use of multiple media elements still make prospective buyers feel confused, because they can not imagine the shape of the house, since all they see is a flat two dimensional (2D) object. To obtain detailed product information house of course they have to visit the exhibition or housing sales office that would spend the time and cost. This is why the authors proposed an application that can display 3D images over the Internet by using Augmented Reality technology, so that prospective home buyers can access these applications anytime and anywhere.